2023
DOI: 10.3390/ijerph20053966
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Women’s Agency on Accessing and Using Maternal Healthcare Services: A Systematic Review and Meta-Analysis

Abstract: Agency, defined as the ability to identify one’s goals and act upon them, has been recognized as a prominent strategy to access maternal healthcare services (MHS). The purpose of this study was to synthesize evidence of the association between women’s agency and MHS utilization. A systematic review was performed on five academic databases, comprising Scopus, PubMed, Web of Science, Embase, and ProQuest. Meta-analysis was performed with a random-effects method using the STATA™ Version 17 software. A total of 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Additionally, factors such as gender, power and agency may have an influence on MNH, decision-making and care-seeking ( Manda-Taylor et al , 2017 ; Amosse et al. , 2023 ; Vizheh et al , 2023 ). Low- and middle-income countries (LMICs) have become a setting of particular focus for these MNH CE activities largely due to the fact that this is where the majority of global maternal and neonatal deaths occur ( Silver and Singer, 2014 ; Langer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, factors such as gender, power and agency may have an influence on MNH, decision-making and care-seeking ( Manda-Taylor et al , 2017 ; Amosse et al. , 2023 ; Vizheh et al , 2023 ). Low- and middle-income countries (LMICs) have become a setting of particular focus for these MNH CE activities largely due to the fact that this is where the majority of global maternal and neonatal deaths occur ( Silver and Singer, 2014 ; Langer et al.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study confirmed the findings of the Ghana Demographic and Health Survey [31] and Ghana Demographic and Health Survey [44] studies, which found that a woman's education was important in ANC utilisation in Ghana. Also, Vizheh et al [14] discovered, through an analysis of DHS data from Bangladesh, Malawi, Bolivia, and the Philippines, that a woman's education was a key determinant of mothers' use of ANC services, just as Stanton et al [24] did in their review of DHS data from developing countries. The North East Region's high percentage of educated mothers using ANC services calls for girl-child education.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cost of medications may discourage mothers from seeking maternal healthcare services. Additionally, the availability of health personnel and maternal health policies were among the majority of reasons for mothers not using medications while pregnant; the review that follows provides empirical research on why mothers do or will not seek medications and health worker assistance when pregnant [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Parental support may improve self-efficacy among girls and empower them, which could help to exercise their agency and raise their voices against marriage proposals at an early age. Women's agency and decision-making power can lead to better utilization of maternal healthcare and optimal health outcomes ( Vijayaraghavan et al, 2022 ; Vizheh et al, 2023 ). Although self-resistance is important for preventing early marriage, social support, particularly from fathers, is instrumental in stalling the forthcoming marriage proposals ( McDougal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%